2016
DOI: 10.1136/emermed-2015-205637
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sugars versus glucose tablets for first-aid treatment of symptomatic hypoglycaemia in awake patients with diabetes: a systematic review and meta-analysis

Abstract: When compared with dietary sugars, glucose tablets result in a higher rate of relief of symptomatic hypoglycaemia 15 min after ingestion and should be considered first, if available, when treating symptomatic hypoglycaemia in awake patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
0
20
0
3
Order By: Relevance
“…Regarding repeat treatment time, of those who were administered 20 g oral glucose, 55% of participants experienced symptomatic recovery within 5 min. This proportion increased to 89% when the treatment interval was extended to 10 min ; however, as described in the meta‐analysis , neither glucose tablets nor dietary sugars reliably restore euglycaemia within 15 min, as time is required for capillary blood samples to return to normal range.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Regarding repeat treatment time, of those who were administered 20 g oral glucose, 55% of participants experienced symptomatic recovery within 5 min. This proportion increased to 89% when the treatment interval was extended to 10 min ; however, as described in the meta‐analysis , neither glucose tablets nor dietary sugars reliably restore euglycaemia within 15 min, as time is required for capillary blood samples to return to normal range.…”
Section: Resultsmentioning
confidence: 80%
“…That study found that glucose (10 g) produced a greater and more rapid plasma glucose increase (2.1 mmol/l, as compared to 0.8 mmol/l (alanine) and 1.2 mmol/l (terbutaline) at 30 min after ingestion), but glycaemic responses were more transient after glucose than after alanine and terbutaline (duration of 60 min, as compared with >8 h, respectively). A recent meta‐analysis comparing dietary sugar to glucose tablets , which included two of the above studies , as well as studies conducted on paediatric participants, found glucose tablets resulted in higher rates of symptomatic recovery at 15 min than dietary sugars, but concluded that both treatment types may be used. Regarding dosage, a diabetes clinic‐based randomized controlled trial (RCT) compared 15 g and 20 g oral glucose and found that 20 g resulted in greater symptomatic recovery at 10 min than 15 g (89% vs 63%, respectively) and thus in less total glucose requirement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is appropriate to check the blood glucose level 10 to 15 minutes after treatment 5,14,23 . As described in a meta‐analysis, 15 minutes is required to restore the euglycemia reliably 24 . A weight‐based approach was suggested to manage hypoglycemia in children, by the International Society for Pediatric and Adolescent Diabetes, as a dose of 0.3 g/kg of rapidly acting carbohydrates 5 .…”
Section: Discussionmentioning
confidence: 99%